2020
DOI: 10.1038/s41419-020-03134-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MIAT regulates blood tumor barrier permeability by functioning as a competing endogenous RNA

Abstract: Blood–tumor barrier (BTB) presents a major obstacle to brain drug delivery. Therefore, it is urgent to enhance BTB permeability for the treatment of glioma. In this study, we demonstrated that MIAT, ZAK, and phosphorylated NFκB-p65 (p-NFκB-p65) were upregulated, while miR-140-3p was downregulated in glioma-exposed endothelial cells (GECs) of BTB compared with those in endothelial cells cocultured with astrocytes (ECs) of blood–brain barrier (BBB). MIAT inhibited miR-140-3p expression, increased the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The extraction and quantification of mRNA were performed according to procedures described in our previous study ( 13 ). The PrimeScriptTM RT reagent Kit (TaKaRa, Dalian, China) was used to reverse transcript mRNA into cDNA according to the instructions provided.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The extraction and quantification of mRNA were performed according to procedures described in our previous study ( 13 ). The PrimeScriptTM RT reagent Kit (TaKaRa, Dalian, China) was used to reverse transcript mRNA into cDNA according to the instructions provided.…”
Section: Methodsmentioning
confidence: 99%
“…Lipofectamine 3000 (Invitrogen, Foster City, CA, USA) was applied to transfect vectors into A375 and M14 cells according to instructions. G418 (Sigma-Aldrich, St Louis, MO, USA) was used to screen stable transfected cell lines according to procedures described in our previous study ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al showed that silencing HOTAIR could increase BTB permeability by eliminating miR-148b-3p, thereby further reducing the expression of glioma-microvascular endothelial cell tight junction (TJ)-related proteins by targeting USF1 (62). He et al also indicated that MIAT regulated the expression of ZAK to promote the delivery efficiency of doxorubicin across the BTB (63). In addition, the IGF2BP2/ FBXL19-AS1/ZNF765 axis could regulate the permeability of the BTB to improve the antitumor effect of doxorubicin (64).…”
Section: Lncrnas As Reliable Therapeutic Targets Treatment Strategies Involving Lncrnas As Regulators Modulating the Btbmentioning
confidence: 99%